KESANTUNAN BERBAHASA BERDASARKAN PRINSIP KERJA SAMA MAHASISWA ANGKATAN 2018 PRODI PBSI UNM - Juwita Pakri; Akmal Hamsa; Muhammad Saleh (Universitas Negeri Makassar, 2020)
Polite Language Based on the Principles of Student Cooperation Class of 2018 PBSI UNM Study Program. This study aims to describe the scale of language politeness based on compliance with and violations of the principle of cooperation in discussion activities for students of the 2018 PBSI UNM Study Program. This research is a descriptive qualitative research. The results showed that the language politeness scale based on the compliance with the principle of cooperation in the discussion activities of students of the 2018 PBSI UNM Study Program was categorized as varied, namely: polite, moderately polite, less polite, and disrespectful by obeying four maxims, three maxims, and two maxims. Likewise, the scale of language politeness based on violations of the principle of cooperation in discussion activities for students of the 2018 PBSI UNM Study Program has varied categories, namely: moderately polite, insufficient, and impolite with violations of two maxims and one maxim.